(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
on healthcare systems and indicate gaps in care transitions. Medication discrepancies are a leading, preventable cause of these readmissions. Medication reconciliation (MedRec), the process of creating the most accurate list of a patient’s medications and comparing it to current orders, is a critical intervention. This paper evaluates the impact of pharmacist-led MedRec on reducing 30-day all-cause hospital readmissions. Methods: A systematic literature review was conducted using PubMed, EMBASE, and Cochrane Central Register of Controlled Trials for studies published between 2010 and 2023. Randomized controlled trials (RCTs) and observational cohort studies comparing pharmacist-led MedRec to standard care were included. The primary outcome was the rate of 30-day hospital readmissions. Data were pooled using a random-effects meta-analysis model. Results: Twelve studies (5 RCTs, 7 observational) involving 8,542 patients were included. Pharmacist-led MedRec was associated with a statistically significant reduction in 30-day readmissions (Pooled Odds Ratio [OR] 0.67; 95% Confidence Interval [CI] 0.55–0.82; p < 0.001). This represents a 33% relative reduction in odds of readmission. Interventions were heterogeneous but typically involved pharmacist-directed medication history taking at admission, patient counseling at discharge, and post-discharge follow-up. Conclusion: Pharmacist-led medication reconciliation is a highly effective strategy for reducing preventable medication errors during care transitions and significantly lowers the risk of 30-day hospital readmissions. Healthcare institutions should prioritize the integration of clinical pharmacists into transition-of-care teams to improve patient safety and reduce healthcare costs.